STATE REGULATION OF FORMATION AND DEVELOPMENT OF HUMAN CAPITAL UNDER THE CONDITIONS OF INNOVATIVE ECONOMY: THEORETICAL ASPECTS - Tereshchenko , Dina (Theory and Practice of Public Administration, 2019)
The article presents the key conceptual provisions of the human capital theory. It is determined that the modern vision of the definition of “human capital” is based on the works of researchers of the human capital evolutiontheory, these works reflect the gradual change of ideas about its role and place in theeconomic development, understanding of the components that make up human capital, and directions of investment in human capital formation and development. The main directions of investment in human capital at different levels are determined. The role of public administration in the formation and development of human capital in ensuring innovative development of the country is studied. It is substantiated that access to knowledge, its successful use and implementation in innovative products, services and processes are the main sources of competitiveness of the economy and productivity growth. The directions of improvement of public administration are offered in order to ensure the effective innovative activity of the country by improving the quality and quantity of human capital. It is proved that the state policy of human capital development must include the first priority measures of reforming the health care system (insurance, providing medical care), creating an innovative environment in the education system, social support, creating an environmentally safe living environment. It is emphasized that new approaches to understanding the public administration via the formation and development of human capital require the search for the optimal balance of market regulators, state regulation and social control. It is pointed out that it is important to define the model of interaction between business structures and authorities at the state and regional levels and to improve mechanisms (state regulation, social partnership, self-organization, self-regulation, stimulation, etc.) to unlock the human intellectual potential and put into practice innovative priorities of enterprises, industries, territories, country.